MicroRNA breed and parent-of-origin effects provide insights into biological pathways differentiating cattle subspecies in fetal liver - MacPhillamy, Callum; Ren, Yan; Chen, Tong; Hiendleder, Stefan; Low, Wai Yee (Frontiers in Genetics, 2023)
MicroRNAs (miRNAs) play a crucial role in regulating gene expression during key developmental processes, including fetal development. Brahman (Bos taurus indicus) and Angus (Bos taurus taurus) cattle breeds represent two major cattle subspecies with strikingly different phenotypes. We analyzed miRNA expression in liver samples of purebred and reciprocal crosses of Angus and Brahman to investigate breed and parent-of-origin effects at the onset of accelerated fetal growth. We identified eight novel miRNAs in fetal liver samples and 14 differentially expressed miRNAs (DEMs) between purebred samples. Correlation of gene expression modules and miRNAs by breed and parent-of-origin effects revealed an enrichment of genes associated with breed-specific differences in traits such as heat tolerance (Brahman) and fat deposition (Angus). We demonstrate that genes predicted to be targets of DEMs were more likely to be differentially expressed than non-targets (p-value <0.05).